Nanopore sequencing of RAGE gene polymorphisms and their association with type 2 diabetes - Chaurasiya, Arvindkumar H.; Khilari, Ajinkya A.; Kazi, Rubina; Jaiswal, Meera R.; Bhoite, Gouri M.; Padwal, Meghana K.; Momin, Abdulrahaman A.; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (ACS Omega, 2023)
The receptor foradvanced glycation end products (RAGE)is a transmembraneprotein that interacts with its ligands, advanced glycation end products(AGEs). AGEs are elevated in diabetes and diabetic complications,leading to increased oxidative stress and activation of pro-inflammatorypathways facilitated by AGE-RAGE signaling. Polymorphisms inthe RAGE gene can potentially affect AGE-RAGEinteraction and its downstream signaling, which plays a crucial rolein the progression of diabetes and its complications. In this study,we used nanopore sequencing for genotyping of RAGE polymorphism and identified a maximum number of 33 polymorphisms,including two previously unreported novel mutations in a cohort ofhealthy, type 2 diabetics without nephropathy and type 2 diabeticswith nephropathy in order to identify associations. Two novel RAGE polymorphisms in the intron 8 and 3 & PRIME;UTR regionat genomic locations 32181834 and 32181132, respectively, were detectedwith a low frequency. For four previously reported polymorphisms,cross-validation by PCR-RFLP showed 99.75% concordance with nanoporesequencing. Analysis of genotype distribution and allele frequenciesrevealed that five single nucleotide polymorphisms, i.e., rs1800625,rs3131300, rs3134940, rs2070600, and rs9391855, were associated withan increased risk for type 2 diabetes.